2020
DOI: 10.1186/s42483-019-0042-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis in Triticum aestivum infecting wheat dwarf virus reveals the effects of viral infection on phytohormone and photosynthesis metabolism pathways

Abstract: Wheat dwarf virus (WDV), a mastrevirus transmitted by the leafhopper Psammotettix alienus, causes a severe disease in cereal crops. Typical symptoms of wheat plants infected by WDV are yellowing and severe dwarfing. In this present study, RNA-Seq was used to perform gene expression analysis in wheat plants in response to WDV infection. Comparative transcriptome analysis indicated that a total of 1042 differentially expressed genes (DEGs) were identified in the comparison between mock and WDV-inoculated wheat p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 73 publications
(70 reference statements)
2
12
0
Order By: Relevance
“…The downregulation of SAUR72 suggested the possible roles of auxins in antiviral response. Similarly, two-component response regulator encoding ORR22 and ORR4 genes that are involved in cytokinin signalling pathways were upregulated and downregulated, respectively [142]. TGMV TrAP protein and spinach curly top virus (SCTV) C2-encoded TrAP protein expression resulted in inhibition of activity of ADK, a regulator of primary cytokinin responsive genes.…”
Section: Phytohormone Modulationsmentioning
confidence: 99%
“…The downregulation of SAUR72 suggested the possible roles of auxins in antiviral response. Similarly, two-component response regulator encoding ORR22 and ORR4 genes that are involved in cytokinin signalling pathways were upregulated and downregulated, respectively [142]. TGMV TrAP protein and spinach curly top virus (SCTV) C2-encoded TrAP protein expression resulted in inhibition of activity of ADK, a regulator of primary cytokinin responsive genes.…”
Section: Phytohormone Modulationsmentioning
confidence: 99%
“…Systematical infection with CMV or CMV mutants brings about some common physiological changes in host plants. Previous studies revealed that the virus infection can modify photosynthesis and disturb chloroplast components and functions [ 49 , 50 , 51 , 52 ], and coat protein of CMV is responsible for the chlorosis in infected leaves [ 51 ]. Indeed, we found numerous genes implicated in photosynthesis and chloroplast organization reduced expression pattern in CMV-infected plants ( Figures S2–S7 ).…”
Section: Discussionmentioning
confidence: 99%
“…This approach is essential for characterizing the plant’s physiological response to pathogens and elucidating the signaling events during pathosystem development. For example, NGS revealed a candidate gene network underlying the resistance of barley to Blumeria graminis [ 113 ], unraveled the broad spectrum of potential molecular events associated with plant susceptible response to Pectobacterium atrosepticum -caused infection [ 114 ], elucidated gene expression patterns that are characteristic of compatible and incompatible interactions between potato plants and Phytophthora infestans [ 115 ], and pointed to the effects of viral infection on phytohormone metabolism [ 116 ], etc. In addition, NGS is also used to study non-infectious diseases and plant adaptation to unfavorable abiotic conditions.…”
Section: Transcriptomicsmentioning
confidence: 99%